Application of Electric Impedance Tomography （EIT） Technology in Critical Respiratory Rehabilitation - PAN Huaping (康复学报)
Electric Impedance Tomography (EIT) technology is comprehensively explored in this study, emphasizing its non-invasive, real-time, dynamic, and radiation-free capabilities for lung ventilation monitoring at the bedside. The exploration encompasses the fundamental principles of EIT including physical, mathematical, and medical aspects, alongside its commonly utilized clinical monitoring functionalities and applications in the rehabilitation of critical respiratory diseases. This study aims to offer insights into the clinical rehabilitation application of EIT technology. Key clinical monitoring functionalities of EIT predominantly entail lung ventilation monitoring, encompassing both spatial and temporal parameters, as well as perfusion distribution monitoring. In the context of critical respiratory disease rehabilitation, EIT finds application in early rehabilitation activity safety assessment, guiding the formulation of respiratory rehabilitation plans, and dynamically assessing rehabilitation effectiveness. This includes providing precise guidance for lung recruitment, airway clearance therapy, respiratory muscle training, individualized ventilation settings, and evaluating the effects of respiratory rehabilitation interventions. Limitations in the application of EIT for critical respiratory diseases rehabilitation primarily include insufficient image stability and the impact of signal reconstruction on monitoring effectiveness, alongside the absence of consensus on personalized adjustment of EIT settings, the necessity for further validation of effectiveness and safety, and the absence of standards and norms in parameter interpretation and examination reporting. Future efforts should prioritize optimizing EIT technology, advancing data fusion techniques, and establishing international standards and guidelines for its utilization to achieve personalized and refined management throughout the entire critical care rehabilitation process using EIT.